Makna dan Pesan yang Terkandung dalam Iklan Video Sirup Marjan pada Ramadhan 1442 H (Sebuah Kajian Semiotika) - Inda Milyana Sari; Pramudita Budi Rahayu (Journal of Communication Sciences (JCoS), 2022)
The study aimed to determine the message and meaning contained in the Marjan 1442 H advertisement using Roland Barthes' theory of denotation, connotation, and myth. The research used a qualitative approach with descriptive analysis, and the data was the advertisement itself. The results showed that the denotational meaning of the advertisement was a new superhero named Reogman, who unites to maintain peace and security in society by defeating the villain named Codot Bati. The connotative meaning was unity in maintaining peace and security symbolizes togetherness and success. The mythic meaning was to always maintain unity and togetherness in society, as unity is not only a source of strength but also important for survival. The message contained in the advertisement was to help each other, maintain unity, and work together. A united society will live in peace and harmony, without animosity and division. Togetherness, mutual assistance, and cooperation are very important in the survival of society and will lead to harmony and peace.